Chronic inflammation degrades CD4 T cell immunity to prior vaccines in treated HIV infection - Kießling, Melissa; Cole, John J.; Kübel, Sabrina; Klein, Paulina; Korn, Klaus; Henry, Amy R.; Laboune, Farida; Fourati, Slim; Harrer, Ellen; Harrer, Thomas; Douek, Daniel C.; Überla, Klaus; et al. (Nature Communications, 2024)
To date, our understanding of how HIV infection impacts vaccine-induced cellular immunity is limited. Here, we investigate inflammation, immune activation and antigen-specific T cell responses in HIV-uninfected and antiretroviral-treated HIV-infected people. Our findings highlight lower recall responses of antigen-specific CD4 T cells that correlate with high plasma cytokines levels, T cell hyperactivation and an altered composition of the T subsets enriched with more differentiated cells in the HIV-infected group. Transcriptomic analysis reveals that antigen-specific CD4 T cells of the HIV-infected group have a reduced expression of gene sets previously reported to correlate with vaccine-induced pathogen-specific protective immunity and further identifies a consistent impairment of the IFNα and IFNγ response pathways as mechanism for the functional loss of recall CD4 T cell responses in antiretroviral-treated people. Lastly, in vitro treatment with drugs that reduce inflammation results in higher memory CD4 T cell IFNγ responses. Together, our findings suggest that vaccine-induced cellular immunity may benefit from strategies to counteract inflammation in HIV infection.
CRIS-Team Scopus Importer:2024-12-06